Evolution of the Coleman Technique. Issue 2 (6th June 2022) - Egro, Francesco M.; Roy, Eva; Rubin, J. Peter; Coleman, Sydney R.
Abstract : Summary: Fat grafting is one of the most revolutionary surgical techniques of our century, and it has changed the field of plastic surgery and regenerative medicine. Early reports of fat grafting date back to the late nineteenth century, but the results were unsatisfactory because of minimal graft retention. It was not until Sydney R. Coleman challenged the dogma and introduced a standardized approach to fat grafting after years of research and learning from experts across the world. The Coleman technique represents an evolutionary approach to fat grafting, with three main components: harvesting, refinement, and placement. The Coleman technique has been adopted and modified by surgeons around the world because it has allowed a reliable increase in fat graft survival through a standardized process. This article discusses the influencing factors and milestones that led to this world-known technique, in addition to Dr. Coleman's current practices, pearls, pitfalls, and lessons learned over the years. The knowledge of the true potential and usefulness of fat is in its infancy, with its regenerative potential becoming increasingly recognized. Current and future research will likely prove that autologous fat has many clinical applications beyond its well-known aesthetic and reconstructive benefits and extending beyond the regenerative realm.